Early clinical development of epidermal growth factor receptor targeted therapy in breast cancer. (3rd April 2017) - Matsuda, Naoko; Lim, Bora; Wang, Xiaoping; Ueno, Naoto T.
ABSTRACT: Introduction : Epidermal growth factor receptor (EGFR) targeted treatment has been evaluated but has not shown a clear clinical benefit for breast cancer. This review article aims to consider the knowledge of the biological background of EGFR pathways in dissecting clinical studies of EGFR targeted treatment in breast cancer. Areas covered : This review focuses on the role of the EGFR pathway and the investigational drugs that target EGFR for breast cancer. Expert opinion : Recent studies have indicated that EGFR targeted therapy for breast cancer has some promising effects for patients with triple-negative breast cancer, basal-like breast cancer, and inflammatory breast cancer. However, predictive and prognostic biomarkers for EGFR targeted therapy have not been identified. The overexpression or amplification of EGFR itself may not be the true factor of induction of the canonical pathway as an oncogenic driver of breast cancer. Instead, downstream, non-canonical pathways related to EGFR may contribute to some aspects of the biological behavior of breast cancer; therefore, the blockade of the receptor could result in sufficient suppression of downstream pathways to inhibit the aggressive behavior of breast cancer. Mechanistic studies to investigate the dynamic interaction between the EGFR pathway and non-canonical pathways are warranted.